The Regional Cancer Centre : developing nationwide professional network for coordinated cancer treatment - Iwashita, Kaou, (SAGE Business Cases., 2018)
The case highlights the bi-directional causal relationship between job quality and innovations in the hospital sector. It focuses on The Regional Cancer Care (RCC) South, a unit that developed and coordinated the cancer care at hospitals in the Southern Healthcare Region in Sweden. This unit aimed to foster the exchange of knowledge and expertise of the cancer care professionals on a national level. Simultaneously, it played a role in disseminating the innovations across the regional hospitals.